The Effectiveness of Traditional Village (Desa Adat) Roles in Spatial Use Control at the Ceking Rice Terrace Tourism Area, Tegallalang, Gianyar - Laura Vianthi; Desak Made Sukma Widiyani (Architectural Research Journal, 2026)
The Ceking Rice Terrace tourist area in Tegallalang, Gianyar is one of Bali's iconic agrotourism destinations, relying on the scenic beauty of terraced rice paddies as its primary attraction. As tourist visits increase, pressure on spatial utilization in this area intensifies, potentially threatening the preservation of the terraced paddies and the ecological-cultural balance of the local community. Desa Adat (Traditional Village) Tegallalang holds authority based on awig-awig and pararem, reinforced by Bali Provincial Regulation Number 4 of 2019 on Traditional Villages. This study aims to analyze the effectiveness of the Traditional Village's role in controlling spatial utilization in the tourist area. A qualitative descriptive method with a case study approach was employed through field observations, in-depth interviews, and review of customary regulatory documents. The findings indicate that the Traditional Village has performed its control function through awig-awig, area arrangement pararem, and co-management with subak; however, its effectiveness remains constrained by weak coordination with local government, economic pressure from tourism businesses, and limited institutional capacity. This study recommends strengthening collaboration between Desa Adat, Desa Dinas, and local government within a spatial control system grounded in the Tri Hita Karana values.